Influence of environmental variables on the benthic macrofauna of sandy beaches - Santos, Marcos Eduardo Miranda (2019)
The beach environment is undoubtedly one of the most dynamic systems that existe. The beaches connect continents and oceans and harbor a wide range of terrestrial and marine species, many of which are used for human consumption and other purposes of great ecological and economic importance. They are formed by several minerals originated from the wear of terrestrial rocks by the action of the waves; wind or river transport; or even produced by living organisms. In addition, they are unstable environments that undergo interference from a wide range of abiotic factors, which in turn have a broad spectrum of variations on short (diurnal) or long (annual) time scales. There is already a wide range of information about the sandy beaches, however, they are scattered confusing students and researchers in this area. Therefore, a brief synthesis of the knowledge already produced about this environment is presented, focusing on the influence of environmental variables on the macrofauna benthic these ecosystems.